Knee Pain among Iranian Industrial Workers, Prevalence and Its Associations with Physical and Psychosocial Work Exposures; Experience from a Developing Country in Industrial Transition - M Ghaffari; A Alipour; AA Farshad; I Jensen; E Vingard (Tehran University of Medical Sciences, 2005)
Objectives: To determine the prevalence of Knee Pain among Iranian industrial workers and how it varies with demographic factors, job title, and gender. To determine work exposure differences between occupational groups, and to explore associations between Knee pain and physical and psychosocial factors at work, as well as lifestyle factors. Summary of background data. Most knee Pain epidemiological data is related to developed and industrialized countries with high income and there is very little information about Knee Pain in the general population in developing and low-income countries. There are even fewer studies in working populations. Methods: All 18031 employees from the largest Industrial group in Iran were included and 77.7% responded. The prevalence of Knee Pain, work exposures and lifestyle factors were recorded according to the standardised Nordic Questionnaire for analysis of musculoskeletal symptoms. Demographic data and lifestyle factors (age, sex, education, weight, work experience, smoking, fitness training) were also collected. Multiple logistic regression model analyses were applied to determine the risk indicators. Results: The majority of this study population are young males (under 30) and a small proportion of the work force is female (4%). The one-year prevalence of self-reported Knee Pain in the Iranian industrial population was 22.9 % (Males=22.7, Females= 25.9). The one-week prevalence was 9.2 % and prevalence rate of absence due to low back pain was 4.5%. In the multiple logistic regression models, heavy lifting, repetitive work, no encouraging organizational culture and monotonous work were significant risk factors for Knee Pain in the previous 12 months. Conclusions: Knee Pain is common among industrial workers in Iran, but in comparison to western countries, there is a considerable difference in prevalence. Work-related physical and psychosocial factors influenced the prevalence of Knee Pain. In order to better understand the natural course of Knee Pain in a working population in developing countries further longitudinal studies for measuring, prevalence, incidence and recurrence simultaneously are recommended.